2016
DOI: 10.1681/asn.2014121184
|View full text |Cite
|
Sign up to set email alerts
|

Erythropoietin Synthesis in Renal Myofibroblasts Is Restored by Activation of Hypoxia Signaling

Abstract: Erythropoietin (Epo) is produced by renal Epo-producing cells (REPs) in a hypoxia-inducible manner. The conversion of REPs into myofibroblasts and coincident loss of Epo-producing ability are the major cause of renal fibrosis and anemia. However, the hypoxic response of these transformed myofibroblasts remains unclear. Here, we used complementary in vivo transgenic and live imaging approaches to better understand the importance of hypoxia signaling in Epo production. Live imaging of REPs in transgenic mice exp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
176
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 144 publications
(185 citation statements)
references
References 60 publications
8
176
1
Order By: Relevance
“…In contrast, a larger proportion of cortical and outer medullary EGFP + Epo -cells expressed the P0 lineage (14), it is plausible that non-P0 lineage interstitial cells with EPO-producing capacity are derived from FOXD1 stromal cells that existed prior to E13.5. PDGFRB is a well-recognized marker of both pericytes and REPCs, and recent imaging studies support the notion that renal pericytes are capable of synthesizing EPO (28). In our genetic model of Foxd1-Cre-mediated Phd2 inactivation we detected Pdgfrb transcripts in approximately 80% of Epo-expressing interstitial cells, suggesting that PDGFRB may not be an exclusive marker of REPCs.…”
Section: Discussionsupporting
confidence: 75%
See 2 more Smart Citations
“…In contrast, a larger proportion of cortical and outer medullary EGFP + Epo -cells expressed the P0 lineage (14), it is plausible that non-P0 lineage interstitial cells with EPO-producing capacity are derived from FOXD1 stromal cells that existed prior to E13.5. PDGFRB is a well-recognized marker of both pericytes and REPCs, and recent imaging studies support the notion that renal pericytes are capable of synthesizing EPO (28). In our genetic model of Foxd1-Cre-mediated Phd2 inactivation we detected Pdgfrb transcripts in approximately 80% of Epo-expressing interstitial cells, suggesting that PDGFRB may not be an exclusive marker of REPCs.…”
Section: Discussionsupporting
confidence: 75%
“…This discrepancy is explained by the very small number of renal interstitial cells targeted with the use of the Epo-Cre transgene. The ability of PHD inhibition to protect the kidney's EPOproducing ability under injury conditions suggests that pharmacologic HIF activation increases EPO synthesis in fibrotic kidneys either by converting non-EPO-producing renal interstitial cells into REPCs, or, as proposed by Souma and colleagues, by maintaining Epo transcription in EPO-producing cells that are undergoing myofibroblast transformation (28). The possibility that even severely diseased kidneys do not completely lose their ability to synthesize EPO in response to HIF-2 activation has been suggested based on studies in CKD patients whose serum EPO levels increased upon ascent to high altitude or following treatment with HIF-2α-stabilizing compounds (30)(31)(32).…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In contrast, the expression of HIF-2α in the hypoxic kidney is limited to the endothelial and interstitial cells. Recent studies have revealed that renal erythropoietin (EPO) is produced in fibroblast-like cells in the interstitium in a HIF-2α-dependent manner [17][18][19].…”
Section: Hypoxia In the Kidneymentioning
confidence: 99%
“…Moreover, the pharmacological inhibition of the PHD in CKD patients stimulates endogenous EPO production further supporting a deranged oxygen sensing [27]. A recent study in mice by Souma et al [48] also strengthened this hypothesis, by showing that inflammatory cytokines and/or fibrosis factors suppress HIF activation through the over-activation of PHD even under pathologic hypoxic conditions, and that the inhibition of PHD restores EPO production.…”
Section: Hypoxia and Progression Of Renal Diseasementioning
confidence: 91%